Contemporary theological approaches in Zimbabwe: Navigating the challenges of the 21st century - Ezekiel Baloyi (HTS Teologiese Studies/Theological Studies)
The challenges of the 21st century are examined as Zimbabwe’s modern theological views are discussed, and responses are given and analysed in this study. In Zimbabwe, theology is changing quickly to meet the demands of the country’s people in the face of persistent socioeconomic difficulties, political unrest and cultural changes. Contemporary theological debate is structured by the historical background of Zimbabwean theology, which is characterised by colonial influences and the freedom movement. These days, the discussion tackles several urgent issues: gender justice, seen through the prism of feminist theology that seeks to demolish patriarchal structures; political unrest, highlighted by a prophetic theology that challenges corruption and fosters governance; the ongoing economic crisis, arguing for economic justice and ethical leadership; and the significance of interfaith dialogue and cultural integration in a pluralistic society. This study also emphasises how important it is to address the specific issues that young people face, include contemporary digital platforms in religious activities, and involve them in theological conversation. To make theology relevant and transformational, theological views in modern Zimbabwe are distinguished by their receptivity to regional and global shifts. This study makes an overview and analysis of theological responses in Zimbabwe – the case for a theology that is both prophetic and practical one that offers long-term remedies for social change in addition to criticism.